Tomographic and radiographic aspects of an infiltrative mediastinal lymphoma in a domestic cat with acute paraparesis: case report - Zardo, Karen Maciel [UNESP]; Babicsak, Viviam Rocco [UNESP]; Santos, Debora Rodrigues dos [UNESP]; Oliveira, Hugo Salvador [UNESP]; Zanoni, Diogo Sousa [UNESP]; Kairalla, Leonardo Delatorre [UNESP]; Mamprim, Maria Jaqueline [UNESP]; De Souza, Priscilla Macedo [UNESP]; Brandão, Claudia Valeria Seullner [UNESP]; Rocha, Noeme Sousa [UNESP] (Univ Federal Rural Pernambuco, 2011)
Lymphomas are malignant neoplasms resulting from clonal proliferations of lymphocytes, originated from lymphoid organs, but can develop in any organ by the migration of lymphocytes to the organ's tissue. Lymphoma constitutes one of the most common neoplasms in cats. Imaging techniques like radiology, ultrasound and tomography may help in diagnosing and classifying lymphomas. Our objective is to report the radiographic and tomographic characteristics of a mediastinal lymphoma in a cat, which occupied a large thoracic and abdominal area and infiltrated into the medullary canal causing acute paraparesis. The tomographic exam was essential for identifying the mass, its extension and its location, besides identifying how compromised the adjacent structures were, but the histopathological examination was crucial to diagnose the nature of the lesion.
Keywords: mediastinal lymphoma; paraparesis; imaging; feline